Children’s Right to Health in the Climate Crisis: State Obligations, Accountability and Intergenerational Justice - Seyednasseri, MohammadMehdi (Bioethics and Health Law Journal (BHL), 2025)
Climate change has evolved from an environmental concern into a systemic public health crisis with profound human-rights implications. Children, owing to their physiological vulnerability, developmental dependency and limited adaptive capacity, are disproportionately exposed to climate-related harms. This article examines the legal foundations of states’ obligations to protect and fulfil children’s right to health in the context of climate change and seeks to articulate a coherent, child-centred framework for accountability within international human-rights law. This study adopts a descriptive-analytical and comparative legal methodology. It draws upon international human-rights treaties, general comments and interpretive outputs of treaty bodies particularly under the Convention on the Rights of the Child and the International Covenant on Economic, Social and Cultural Rights alongside UN and specialized agency reports, peerreviewed legal scholarship and relevant international and regional jurisprudence. The analysis demonstrates that: 1. climate change poses multidimensional threats to children’s physical and mental health through heat stress, air pollution, food and water insecurity, displacement and climate-induced disasters; 2. international human-rights law provides a robust normative basis for delineating states’ positive, negative and duediligence obligations regarding children’s health; 3. a persistent implementation gap exists between legal commitments and domestic practice, largely attributable to inadequate child-sensitive governance, fragmented policy responses and weak monitoring mechanisms; 4. emerging climate litigation initiated by children and youth has begun to reshape accountability narratives, though its effectiveness depends on parallel legal and institutional reforms. Ensuring children’s right to health in the era of climate change requires a recalibration of legal and policy frameworks toward explicit child sensitivity. This entails strengthening international and domestic legal norms, enhancing monitoring and adjudicative mechanisms responsive to climate-related health harms and mainstreaming child-centred considerations into mitigation and adaptation strategies. The study underscores the necessity of mandatory child-focused climate impact assessments, improved child-specific data systems and meaningful participatory avenues for children as rights-holders in climate governance.